Editorial: “Crossing boundaries: stem cells, materials, and mesoscopic sciences” - Ho, Anthony Dick; Nakatsuji, Norio (Biotechnology journal, 2012)
This Special Issue, edited by Prof. Anthony Ho and Prof. Norio Nakatsuji, comprises review articles on the interdisciplinary study of stem cells and material science and is a celebration of the friendship and collaboration between Heidelberg University and Kyoto University in Germany and Japan, respectively.